Dentin-derived alveolar bone graft for alveolar augmentation: A systematic review - Dedy Agoes Mahendra; Kavanila Bilbalqish; Alexander Patera Nugraha; Arief Cahyanto; Kaushik Sengupta; Kamal Hanna; Asti Meizarini; Ninuk Hariyani (Elsevier, 2024)
Introduction: Application of alveolar bone graft (ABG) in alveolar augmentation is done to prevent excessive bone resorption due to tooth extraction, missing teeth, or other diseases/conditions affecting the alveolar bone. The use of autogenous dentin-derived ABG has been considered as the composition of dentin appears to be nearly analogous to that of bone. Objective: This systematic review aims to assess the efficacy of dentin-derived ABG for alveolar augmentation of post-extraction sockets or other alveolar bone defects by evaluating volume gain and histomorphometric data. Material and methods: A search of systematic literature was conducted in Pubmed, Scopus, Web of Science, and Embase from database inception to October 2023. The review included both randomized controlled trials (RCT), pilot studies, clinical trials, and retrospective studies reporting on dentin-derived ABG use for alveolar augmentation. Results: Overall, 298 articles were obtained from the initial search. From these articles, 21 articles met the inclusion criteria and were included for descriptive analysis. All of the studies indicated low risk of bias. Studies of dentin-derived ABG, which used bone-derived grafts as the control group, have shown significantly higher percentages of new bone formation, gain in vertical and horizontal dimensions, and less reduction in dimensions. Conclusions: Dentin-derived ABG was effective in volume maintenance, indicating promising results via histomorphometric and radiographic analysis.